Hijras, lovers, brothers: surviving sex and poverty in rural India - Saria, Vaibhav (Thinking from elsewhere, 2021)
Introduction: that limpid liquid within young men -- Prodigious birth of love -- In false brothers, evil awakens -- Interlude: standing at a slight angle to the universe -- Something rotten in the state -- Love may transform me -- I have immortal longings in me.